Staged Repair of Van Praagh Truncus Type A3. Issue 2 (March 2021) - Ganta, Srujan; Duster, Nicole; El-Said, Howaida; Artrip, John; Rao, Rohit; Golding, Ian; Dummer, Kirsten; Nigro, John J.
Van Praagh (VP) A3 variant of truncus arteriosus (or common arterial trunk) is defined by only one pulmonary artery (usually the right) originating from the common trunk, while the other lung is supplied either by collaterals or a pulmonary artery arising from the aortic arch. This report describes a staged approach to manage a VP-A3 variant truncus arteriosus with ductal origin of the left pulmonary artery (LPA), a hypoplastic right pulmonary artery, and cyanosis. Initially, the ductal portion of the proximal LPA was stented with a Resolute Onyx drug-eluting stent. The pulmonary arteries grew and at four months of age had an acceptable McGoon ratio and Nakata index. The patient then underwent repair which included unifocalization of the branch pulmonary arteries, closure of the ventricular septal defect, and placement of a right ventricle-to-pulmonary artery homograft conduit.